Extreme Wave Analysis for the Dubai Coast - Khaled Elkersh; Serter Atabay; Abdullah Gokhan Yilmaz (Hydrology, 2022)
This paper aims to present the result of commonly used extreme wave analysis distribution methods applied to a long-term wave hindcast at a point in the Arabian Gulf near the coastline of Dubai, United Arab Emirates. The wave data were hindcasted for a total period of 40 years, starting from 1 January 1979 to 31 December 2018. This analysis aims to support the design, repair, and maintenance of coastal structures near the Dubai coast. A 2.5 m threshold is selected using the Peak Over Threshold method to filter the storm data for the extreme wave analysis. Different distribution methods are used for this analysis such as Log-normal, Gumbel, Weibull, Exponential, and Generalized Pareto Distribution (GPD). The significant wave heights are predicted for different return periods. The GPD distribution appears to fit the data best compared to the other distribution methods. Many coastal projects are being planned near the Dubai coastline. Hence, the analysis presented in this paper would be useful in designing safe and efficiently designed projects.